Evidence of a shared purpose, critical reflection, innovation and leadership in interprofessional healthcare teams: a realist synthesis. Issue 3 (May 2015) - Sims, Sarah; Hewitt, Gillian; Harris, Ruth
Abstract Realist synthesis is a theory-driven approach for evaluating complex interventions using empirical evidence, which seeks an explanatory analysis of who a complex intervention works for, how, why, and in what circumstances. Interprofessional teamworking in healthcare is one such complex intervention, as teams are influenced by social and organizational factors, which makes them highly variable and context dependent. This article concludes a series of four articles that report on a realist synthesis of interprofessional teamworking. The synthesis identified 13 mechanisms that are reported in the literature to be the underlying processes through which interprofessional teamworking produces its effects. This article explores four of these mechanisms: a shared purpose; critical reflection; innovation; and leadership. These mechanisms together explain how a team sets and maintains its focus and direction. This article highlights that whilst many assumptions are made within the healthcare literature about how these mechanisms operate within teams, these assumptions are not always founded upon strong empirical evidence.